HISTOLOGICAL CHANGES ON THE LUNG OF THE OFFSPRING FROM MOTHERS TREATED WITH URANYL ACETATE IN ALBINO RATS - Alwachy, Sabah N; Othman, Himen H; Othman, Himen H; Amir, Nusaiba (Al-Nahrain Journal of Science, 2010)
This study was carried out to investigate the toxicity of the oral administration of uranyl acetateon the activity of some vital organs. Twenty mature females and ten males of albino ratswere used in this experiment. They were divided into four equal groups. The first group (G1)used as control received only distilled water, while the others administrated orally by (50, 75 and100 mg/kg/b.w. /day of uranyl acetate) for 70 days (10 weeks). Lung was taken from the offspringat two age stages (3rd and 5th weeks) for the current study.Rats exposed to different doses of uranyl acetate showed a significant (p